The role of the private sector in the promotion of young entrepreneurship in Nigeria - Nwoye, May Ifeoma (Technovation)
Several strategies have been employed in Nigeria in an effort to develop economic growth. This study shows that the private sector, as opposed to the public sector, is the major growth area for developing entrepreneurship.